Analysis of Road User Satisfaction with Road Congestion: A Case Study on Jalan Duyung in front of Batu Ampar Port - Rico Sinaga; Mulia Pamadi (Fakultas Teknik Sipil dan Perencanaan, 2023)
Road congestion is a severe problem faced in many big cities worldwide. This study aims to analyze road users' satisfaction level with road congestion and the factors that contribute to their perceptions of Jalan Duyung in front of Batu Ampar Harbor in Batam City. Roads should be balanced with the adequacy and availability of transportation infrastructure and facilities to prevent traffic problems. Traffic lights aim to optimize and regulate traffic to run optimally. Based on research that has been done, traffic jams can have an impact on the economy, psychology, and productivity of road users.